TANTANGAN DAN PELUANG PENERAPAN ACTIVITY-BASED COSTING UNTUK EFISIENSI PELAYANAN KESEHATAN DI RUMAH SAKIT - May Hana Bilqis Rangkuti; Yeti Meliany Lubis; Simpati Mellyginta Sinuhaji (Jurnal Keluarga Sehat Sejahtera, 2025)
Hospitals face the challenge of delivering high-quality healthcare services while maintaining cost efficiency. One relevant managerial accounting approach is Activity-Based Costing (ABC), which allocates costs based on activities. This article examines the opportunities and challenges of implementing ABC in hospitals through a literature review of national and international journals, textbooks, and relevant regulations. The findings indicate that ABC can improve the accuracy of cost information, support cost control, and facilitate strategic decision-making. However, its implementation encounters obstacles such as the complexity of medical services, limited human resources, and the need for adequate information technology infrastructure.